GeoCapabilities, Didaktical analysis and curriculum thinking – furthering the dialogue between Didaktik and curriculum. Issue 3 (2nd July 2020) - Bladh, Gabriel
Abstract: One of the ideas of the GeoCapabilities project(s) is to open up an international debate on the purposes and values of geography education. In line with this, the aim of this article is to examine some central perspectives used in GeoCapabilities, such as curriculum thinking, the teacher as 'curriculum maker' and the perspective of powerful knowledge, and explore them in relation to the continental and Nordic traditions of Didaktik and subject matter didactics. This is especially done through a reading of the German educationalist Klafki and his theory of categorial Bildung and an application of his framework of Didaktical analysis. This highlights how the perspectives of powerful knowledge and capabilities in GeoCapabilities mirror the perspectives on material and formal Bildung by Klafki. Drawing on his idea of educational potential and exemplary relevance, an example of knowledge-led curriculum thinking in geography is presented using a case based on the time-geographical perspective for a brief Didaktical analysis. Such exemplary cases can function as subject didactical models for curriculum thinking. The article concludes with some remarks on the knowledge turn and indicates some future challenges for geography education.